An overview of accessibility measures - Mateus Araújo E Silva; Eiji Kawamoto (European Regional Science Association (ERSA), 2010)
This paper presents a review of accessibility measures in transportation studies by addressing its conceptual framework, data requirements, and applications. Depending on the theoretical basis, the accessibility measures are classified, in infrastructure, location, gravity, space-time and utility-based measure. A system approach is applied to identify the relations among the interacting variables: land use, transportation, temporal and individual. The criteria, including theoretical basis, interpretability, and data requirements are used to evaluate these measures. Recent progress in accessibility studies point towards the inclusion of more individual's spatial-temporal accessibility measure (using the space-time prism concept) but the data requirements, and interpretability of this measure remains as a problem. Furthermore, most of the measures for not considering the competition for opportunities (e.g. jobs on the employment market), and it seems to be the main issue for the development of more realistic accessibility measures.
Keywords: 330